Strategies of psychotherapy / Jay Haley - Haley, Jay
This classic volume deals with the strategies of both psychotherapists and clients as they maneuver each other in the process of treatment. How a therapist induces a client to change is described within a framework of interpersonal theory and directive family therapy. This work represents a step from the study of therapy in terms of the individual to therapy as communication between at least two people. In this volume, Jay Haley acknowledges his debt to the Gregory Bateson research project exploring the nature of communication as well as to Dr. Milton H. Erickson, M.D. for the many hours of conversations and a new perspective on the nature of therapy. The reactions to this different view continue to be controversial today in the therapy field.